YAKKUMON TEA: Development of a Functional Tea Based on Dayak Onion, Banana Peel, and Lemon as a Preventive Strategy Against Hypertension - Sofiyah Annisa; Harlyanti Mashar; Rizky Kusuma Wardani; Tesalonika Kanomeira Farrell Boy Garang; Mikhael Rukhandra Panarang Tarung (Journal of Noncommunicable Diseases Prevention and Control, 2026)
Hypertension is one of the non-communicable diseases with a continuously increasing prevalence and contributes to various degenerative complications. Innovative strategies based on local food resources are needed as preventive approaches to support the achievement of Sustainable Development Goal (SDG) 3. This study aimed to develop and analyze the nutritional characteristics and antioxidant activity of Yakkumon Tea, a tea bag product formulated from Dayak onion (Eleutherine palmifolia), banana peel, and lemon, as a potential functional beverage for hypertension prevention. An experimental design was employed, including nutritional content analysis and antioxidant activity testing using the DPPH method to determine the IC₅₀ value. The results showed that each tea bag contained 4.2 kcal of energy, 0.3 g protein, 0.5 g fat, 5.6 g carbohydrates, 0.1 mg vitamin C, 0.8 mg sodium, and 37 mg potassium. The low sodium and relatively high potassium content indicate its potential role in supporting blood pressure control. The antioxidant activity test demonstrated an IC₅₀ value of 85.95 µg/mL, which is categorized as strong antioxidant activity. In conclusion, Yakkumon Tea possesses nutritional characteristics and antioxidant activity that may support hypertension prevention. This product has the potential to be developed as a local food-based functional beverage suitable for individuals at risk of hypertension.